New growth from old rubbish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Many of those with experience of working in agricultural development recognize that the growing use of chemical inputs may often be doing more harm than good to farming and the environment in developing countries. Nevertheless, it is essential that...